2012
DOI: 10.1111/j.1365-2133.2012.11106.x
|View full text |Cite
|
Sign up to set email alerts
|

A multicentre, cross-sectional study on quality of life in patients with cutaneous lupus erythematosus

Abstract: Background A study at the University of Pennsylvania (UPenn) Medical Center demonstrated that quality of life in cutaneous lupus erythematosus (CLE) patients is negatively impacted. Whether CLE patients in other geographic locations have similar quality of life is unknown. Objective We sought to compare quality of life indicators between CLE patients at the University of Texas Southwestern (UTSW) Medical Center at Dallas and UPenn. Methods 248 CLE patients at UTSW (N=91) and UPenn (N=157) completed the Ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
103
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(109 citation statements)
references
References 37 publications
3
103
2
1
Order By: Relevance
“…A large study by Jolly et al further validated the CLASI tool, which has proven to be a valuable resource for research into CLE pathogenesis and treatment [40]. This tool is being used in many international studies and has been shown to be responsive to improvement in disease activity, as well as correlate with quality of life and a number of biomarkers [41-45]. Further physical exam should investigate for signs that may be seen in systemic disease, such as vasculitic lesions.…”
Section: How Can We Properly Diagnose Cle?mentioning
confidence: 99%
“…A large study by Jolly et al further validated the CLASI tool, which has proven to be a valuable resource for research into CLE pathogenesis and treatment [40]. This tool is being used in many international studies and has been shown to be responsive to improvement in disease activity, as well as correlate with quality of life and a number of biomarkers [41-45]. Further physical exam should investigate for signs that may be seen in systemic disease, such as vasculitic lesions.…”
Section: How Can We Properly Diagnose Cle?mentioning
confidence: 99%
“…This result suggests that the QOL of females tended to be worse than males, and is in agreement with previous reports, although the male group in this study was very small. 2,15 Subtypes of LE To assess the relationship between the subtypes of LE and the QOL, we chose SLE and CLE, but excluded MCTD and overlap syndrome because of the complexity of their conditions. The scores from the Skindex-29 decreased significantly after treatment in the three subscales in both SLE and CLE patients (p < 0.005) ( Figure 3).…”
Section: Gendermentioning
confidence: 99%
“…The CLASI™ has been validated against physician- and patient-reported outcomes, including measures of cutaneous damage [5] and quality of life [4]. The latter is especially important to consider in the assessment of these patients, as individuals with CLE have demonstrated a poorer quality of life than those with other common conditions affecting the skin [6] across multiple geographic populations [7]. Worse quality of life in CLE patients is associated with a number of factors including female gender, younger age, presence of facial lesions, and non-responsiveness to treatment [6, 8].…”
Section: Evaluation Of Disease Severitymentioning
confidence: 99%